2022
DOI: 10.1002/smi.3153
|View full text |Cite
|
Sign up to set email alerts
|

Changes in perceived stress during the COVID‐19 pandemic among American veterans

Abstract: American veterans are a population that suffer from both context specific stressors as well as many population‐specific major‐life events. The present exploratory study utilises a longitudinal cohort of 1230 U.S. veterans surveyed from February 2020 through February 2021. We sought to understand heterogeneity in perceived stress, using growth mixture modelling, over this time period, how COVID‐specific factors such as negative reactions to the pandemic, loneliness, and employment disruptions influence perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…In our sample of combat-injured veterans, preexisting depression seemed to be a catalyst of the dynamic associations between pain and perceived stress, such that pain and perceived stress were bidirectionally associated at the within-person level only in those who screened positive for depression. This is in line with the system model of pain's conception of depression as an amplifier of pain and stress symptom dynamics (14), and builds on prior empirical work demonstrating links between depression, pain, and perceived stress among veterans (9,10,24). Although prior prospective studies demonstrated that both perceived stress and depression are associated with subsequent pain among veterans (9,10), our results further clarify how all three variables may be linked.…”
Section: Original Articlesupporting
confidence: 88%
See 4 more Smart Citations
“…In our sample of combat-injured veterans, preexisting depression seemed to be a catalyst of the dynamic associations between pain and perceived stress, such that pain and perceived stress were bidirectionally associated at the within-person level only in those who screened positive for depression. This is in line with the system model of pain's conception of depression as an amplifier of pain and stress symptom dynamics (14), and builds on prior empirical work demonstrating links between depression, pain, and perceived stress among veterans (9,10,24). Although prior prospective studies demonstrated that both perceived stress and depression are associated with subsequent pain among veterans (9,10), our results further clarify how all three variables may be linked.…”
Section: Original Articlesupporting
confidence: 88%
“…Strikingly large numbers of veterans report pain (1,2,40) along with co-occurring perceived stress and depression (10,20,28,29). As many US veterans are currently returning from deployment, it is necessary to improve understanding of the associations between pain and its psychological correlates, as this could inform…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations